SDN: software defined networks : [an authoritative review of network programmability technologies] - Nadeau, Thomas D. (O'Reilly, 2013)
Explore the emerging definitions, protocols, and standards for SDN - software-defined, software-driven, programmable networks - with this comprehensive guide. Two senior network engineers show you what's required for building networks that use software for bi-directional communication between applications and the underlying network infrastructure.